A two-site, two-arm, 34-week, double-blind, parallel-group, randomized controlled trial of reduced nicotine cigarettes in smokers with mood and/or anxiety disorders: trial design and protocol. (December 2017) - Allen, Sophia; Foulds, Jonathan; Pachas, Gladys; Veldheer, Susan; Cather, Corinne; Azzouz, Nour; Hrabovsky, Shari; Hameed, Ahmad; Yingst, Jessica; Hammett, Erin; Modesto, Jennifer; Krebs, Nicolle; et al.
Abstract Background The U.S. Food and Drug Administration can set standards for cigarettes that could include reducing their nicotine content. Such a standard should improve public health without causing unintended serious consequences for sub-populations. This study evaluates the effect of progressive nicotine reduction in cigarettes on smoking behavior, toxicant exposure, and psychiatric symptoms in smokers with comorbid mood and/or anxiety disorders using a two-site, two-arm, double-blind, parallel group, randomized controlled trial (RCT) in four phases over 34 weeks. Methods Adult smokers (N = 200) of 5 or more cigarettes per day will be randomized across two sites (Penn State and Massachusetts General). Participants must have not had a quit attempt in the prior month, nor be planning to quit in the next 6 months, meet criteria for a current or lifetime unipolar mood and/or anxiety disorder based on the structured Mini-International Neuropsychiatric Interview, and must not have an unstable medical or psychiatric condition. After a week of smoking their own cigarettes, participants receive two weeks of Spectrum research cigarettes with usual nicotine content (11.6 mg). After this baseline period, participants will be randomly assigned to continue smoking Spectrum research cigarettes that contain either (a) Usual Nicotine Content (11.6 mg); or (b) Reduced Nicotine Content: the nicotine content per cigarette is progressively reduced from approximately 11.6 mg to 0.2 mg in five steps over 18 weeks. At the end of the randomization phase, participants will be offered the choice to either (a) quit smoking with assistance, (b) continue smoking free research cigarettes, or (c) return to purchasing their own cigarettes, for the final 12 weeks of the study. The primary outcome measure is blood cotinine; key secondary outcomes are: exhaled carbon monoxide, urinary total NNAL- 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol and 1-hydroxypyrene, oxidative stress biomarkers including 8-isoprostanes, measures of psychiatric symptoms (e.g., depression, anxiety), smoking behavior and dependence (e.g., cigarette consumption, quit attempts), and health effects (e.g., blood pressure, respiratory symptoms). Discussion Results from this study will inform FDA on the potential effects of regulating the nicotine content of cigarettes and help determine whether smokers with mood and/or anxiety disorders can safely transition to significantly reduced nicotine content cigarettes. Trial registration TRN:NCT01928758, registered August 21, 2013.